Flexible grazing strategies for sustainable rangeland resources management - Louhaichi, Mounir; Hassan, Sawsan; Gamoun, Mouldi (International Center for Agricultural Research in the Dry Areas, 2022)
To strengthen institutional arrangement that link national developing agencies dealing with rangeland rehabilitation and management with the end users (pastoralists and livestock keepers), representatives from ICARDA, Office de l’Elevage et des Pâturages (OEP), and Tunisia's General Directorate for Forestry (DGF), farmers and pastoralists were invited to a day-long workshop on June 6th, 2022, where participants discussed a flexible approach to grazing management to adopt a new flexible grazing management procedure when implementing gdel on rangelands. This new approach suggests that the duration of livestock grazing exclusion (gdel) should be decided depending on the climatic and the site-specific conditions not on a fixed period (3 years) which will offer a cost-effective intervention to resolving one of technical hurdle on the way toward optimizing the sustainable use of rangelands and strengthening the resilience of the pastoral communities.